A polyoxometalate@covalent triazine framework as a robust electrocatalyst for selective benzyl alcohol oxidation coupled with hydrogen production. Issue 10 (4th January 2021) - Li, Zhen; Zhang, Junhao; Jing, Xiaoting; Dong, Jing; Liu, Huifang; Lv, Hongjin; Chi, Yingnan; Hu, Changwen
Abstract : Electrocatalytic oxidation has been proven as a sustainable and promising alternative to traditional chemical transformation, but its further development is limited by the use of noble-metal electrocatalysts. Abstract : Electrocatalytic oxidation has been proven as a sustainable and promising alternative to traditional chemical transformation, but its further development is limited by the use of noble-metal electrocatalysts. Herein, a polyoxometalate-based electrode material, H5 PMo10 V2 O40 @CTF (denoted as PMo10 V2 @CTF ), has been successfully fabricated through electrostatic assembly of a molecular polyoxometalate catalyst, PMo10 V2, with a porous cationic covalent triazine framework (CTF), which, to our knowledge, represents the first combination of polyoxometalate with a cationic CTF. The resulting PMo10 V2 @CTF exhibits high activity for the selective electrocatalytic oxidation of alcohols to aldehydes, achieving 99% conversion of benzyl alcohol, over 99% selectivity of benzyl aldehyde, and at the same time near unity H2 production. Notably, the reported electrocatalytic system presents good atom economy, high energy conversion (96% faradaic efficiency), remarkable catalytic activity and robustness for at least eight recycles. Based on the various experimental and spectroscopic analyses, a possible catalytic mechanism was proposed, revealing that such excellent electrocatalytic performance is attributed to the versatile redox ability of PMo10 V2 and the good porosity and adsorption property of the CTF in the constructed PMo10 V2 @CTF composite.